VALIDATION METHODS FOR THE ANALYSIS OF HYDROXYPROLINE FROM COLLAGEN UNDENATURED TYPE II COLLAGEN USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY FLUORESCENCE - Maggadani, Baitha Palanggatan; ., Harmita; Lubnan, Milza (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to validate an high-performance liquid chromatography method for analyzing undenatured Type II collagen preparations using a fluorescence detector. Methods: Based on the optimum analysis conditions, the compound was detected at an excitation wavelength of 255 nm and an emission wavelength of 320 nm. The optimum mobile phase was determined to be acetate (pH 4.2) and acetonitrile (60:40) with a flow rate of 1.0 ml/min. Hydroxyproline is a compound that does not have chromophore moiety; thus, it has to be derivatized first using 9-fluorenylmetoxycarbonyl-chloride. Results: The developed method was validated with linearity and an equation of y=3,249,704 x+141,945,072, with a value of r=0.9994. The detected range of hydroxyproline was 4–15 ppm. The limit of detection was determined to be 0.49, with an limit of quantitation of 1.64. Conclusion: Our results indicated that the average level of hydroxyproline was 98.66%, 99.12%, and 99.85%.